Security analysis of continuous-variable quantum key distribution with imperfect Faraday mirror. (17th October 2019) - Liang, Kexin; Cao, Zhengwen; Liu, Weiqi; Wang, Jiayao; Chai, Geng; Zhang, Tongyi
Abstract: For the practical Faraday mirror (FM) in a continuous-variable quantum key distribution (CVQKD) system there exists a rotation angle deviation that can lead to a loss of photon number when a light message passes through the polarization beam splitter. Here we employ the entanglement-based model to research the influence of the FM's imperfection. Based on parameter estimation, the imperfection can introduce a loophole for Eve to obtain information. The secret key rate of the CVQKD will be impaired. Finally, a novel method is proposed to ensure system performance by compensating optical power, and we further study the relationship between the secret key rate and the modulation variance.